2023
DOI: 10.3389/fonc.2023.1126536
|View full text |Cite
|
Sign up to set email alerts
|

Real-world clinical outcomes of nivolumab and taxane as a second- or later-line therapy for recurrent or unresectable advanced esophageal squamous cell carcinoma

Abstract: BackgroundNivolumab is approved in Japan as a second-line treatment for patients with advanced esophageal squamous cell carcinoma (ESCC) resistant to fluoropyrimidine and platinum-based drugs. It is also used in adjuvant and primary postoperative therapies. This study aimed to report real-world data on nivolumab use for esophageal cancer treatment.MethodsIn total, 171 patients with recurrent or unresectable advanced ESCC who received nivolumab (n = 61) or taxane (n = 110) were included. We collected real-world… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Chemotherapy, the most prevalent approach for cancer treatment, exhibits less invasiveness compared to surgery or radiation, exerts relatively minimal overall adverse effects on patients, and demonstrates remarkable efficacy in eradicating tumor cells and preventing metastasis [ 19 , 20 , 21 ]. However, this statement highlights the substantial toxicity and adverse effects on the human body associated with chemotherapy, as well as its propensity to develop drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy, the most prevalent approach for cancer treatment, exhibits less invasiveness compared to surgery or radiation, exerts relatively minimal overall adverse effects on patients, and demonstrates remarkable efficacy in eradicating tumor cells and preventing metastasis [ 19 , 20 , 21 ]. However, this statement highlights the substantial toxicity and adverse effects on the human body associated with chemotherapy, as well as its propensity to develop drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, anti-PD-1 antibody may also be administered in patients who do not meet the eligibility criteria for clinical trials, including patients with poor performance status (PS) or severe comorbidities or elderly populations. Although drug efficacy needs to be assessed in both clinical trials and real-world settings, real-world data on the efficacy and survival of nivolumab monotherapy for unresectable advanced or recurrent ESCC in clinical practice are very limited [ 18 ]. In addition, since the CheckMate 648 trials demonstrated the efficacy of nivolumab as a first-line therapy [ 19 ], combination chemotherapy with nivolumab or a dual immune checkpoint inhibitors is increasingly being used in clinical settings; therefore, the availability of prospective data for nivolumab monotherapy is limited.…”
Section: Introductionmentioning
confidence: 99%